Price bubbles sans dividend anchors: Evidence from laboratory stock markets - Shinichi Hirota; Shyam Sunder (Osaka University, Institute of Social and Economic Research (ISER), 2005)
We experimentally explore how investor decision horizons influence the formation of stock prices. We find that in long-horizon sessions, where investors collect dividends till maturity, prices converge to the fundamental levels derived from dividends through backward induction. In short-horizon sessions, where investors exit the market by receiving the price (not dividends), prices levels and paths become indeterminate and lose dividend anchors; investors tend to form their expectations of future prices by forward, not backward, induction. These laboratory results suggest that investors' short horizons and the consequent difficulty of backward induction are important contributors to the emergence of price bubbles.
Keywords: G12; C91; 330; stock price bubbles; short-term investors; backward induction; market experiments; Börsenkurs; Spekulationsblase; Anlageverhalten; Test